WILLINGNESS TO PAY PETANI TERHADAP BENIH PADI HASIL IRRADIASI BADAN NUKLIR - Rini Desfaryani; Edy Humaidi; I Putu Ajie Windu Kartayoga; Endah Yuni Puspitasari (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2021)
This study aims to analyze the level of availability of farmers paying irradiated rice seeds from the Nuclear Energy Agency (BATAN) and analyze the factors affecting the availability of farmers paying irradiated rice seeds, respondents in this study are farmers who have used irradiated rice seeds with 60 farmers, Data analysis in this study uses Analysis of CVM (Contingent Valuation Method) and Analysis of Structural Equation Modeling (SEM). The results showed the total value of willingness to pay (WTP) consumers of irradiated rice seeds as much as Rp. 116,083 per package (5 kilograms) means 16.08 percent higher than the current price, this condition means the maximum limit of consumers' willingness to pay 16.08 percent higher than the current price. Product attributes and social status are factors that are significantly correlated to the availability of farmers paying (WTP) irradiated rice seeds ( 0.05)